Christianity in Modern Palestine and the Palestinization of the Church: In the light of Elia Khoury - Abu Eid, Xavier Ignacio (Trinity College Dublin. School of Religion, Theology, and Peace Studies, 2026)
This thesis aims at describing the process of the Palestinization of the Episcopal Church of Jerusalem as part of the broader Palestinian struggle for decolonization. Centered on the role of bishop Elia Khoury (Zababdeh 1922 Amman 2004), it provides a description of the position of the Episcopal Church within Palestinian society, the early struggles of the Palestinian congregation and the broad effects of the Nakba on Palestinian Christianity. Drawing on historical, political and theological analysis of Church archives, ecclesiastical documents, political records and theological writings, the thesis focuses on the ecclesiastical, political and theological dimensions of the Episcopal Church, positioning bishop Elia Khoury as a central figure within the Church on one side and the Palestinian national movement on the other. Across its five chapters, the thesis traces the frictions between a colonial Church and a Church of the people, including the latters participation in the national struggle. The Episcopal Church of Jerusalem remained a small Church within the overall Palestinian Christianity. However, the number of its members joining prominent positions in the national movement was entirely overrepresented, as was its role in the development of a Palestinian contextual theology and later, Palestinian liberation theology. In this process, Palestinian theologians tried to interpret the Bible through Palestinian eyes, especially after the faith crisis brought about by the Nakba of 1948 and the Israeli occupation of 1967. This includes not only the contradictions faced domestically between Palestinian communities, whether in the homeland or in exile, but also disputes between Palestinian Christians and foreign Churches that either endorsed or tolerated the Zionist project in Palestine. Overall, this thesis presents a severely under-studied perspective on the Palestinian national movement by analysing the specific role that Churches and Christian figures in the struggle for decolonization. It conceptualizes Christian struggles as a dual one: On the one hand, resistance to the foreign occupation of the Church, and on the other, resistance to the foreign occupation of the homeland. Bishop Elia Khoury, a refugee in 1948, a prisoner after 1967 and an exile until his death in Jordan, represents the only Christian ecclesiastical figure that accepted to have leadership roles in both the liberation movement and the Church. He reached to the top of the Palestine Liberation Organization (PLO) in its executive committee, deputy speaker of the Palestine National Council (PNC) and bishop in the Jerusalem Episcopal bishopric. In light of this, the thesis demonstrates his contributions to the Palestinian national movement from various perspectives. Through Elia Khoury, alongside other members of the clergy, it becomes clear that they did not see their struggle for a Palestinian Church and social justice as separate from the broader struggle for a free Palestine, the rights to justice, self-determination and return.
APPROVED